The Spirituality of Elementary School Teachers in Indonesia in Teaching Visual Arts - Ramlan, Ramlan (International Journal Labs, 2025)
It is indicated that art education in Indonesian schools is considered less important by policymakers or curriculum developers compared to other subjects such as mathematics, science, and English. As a result, art teachers in elementary schools often carry out their teaching without seriousness or alignment with the intended learning objectives. This study employs the